MODEL PENDIDIKAN AGAMA “ALA PESANTREN” BAGI WARGA BINAAN (NARAPIDANA) DI LEMBAGA PEMASYARAKATANKALIMANTAN SELATAN - Muhniansyah Arasyid Mahani (ADIBA : JOURNAL OF EDUCATION, 2025)
It is not easy to educate and train inmates. This is because most of them come from members of society who have low education and minimal religious insight. Various efforts have been made by the government through this institution so that they realize the error of their actions and do not repeat their actions after serving their sentence. Recidivist is the term for those who have been in a correctional institution but after being released, they repeat it again. Not a few have recidivist status. It can be interpreted that while serving prison time and undergoing education did not have a positive impact on them. Therefore, innovative or new models are needed in educating them so that they do not make mistakes again. Their low level of education and lack of awareness and knowledge of their religion are clues to making them aware of the aspect of their education. Islamic religious education provided in correctional institutions is felt to be useful in changing the attitudes and behavior of inmates. Some religious education activities that have been carried out in correctional institutions and detention centers are as follows: Learning to read the Koran (Qur'an) in the form of learning IQRA, learning tahsin, learning recitations, tahfiz Qur'an (juz amma, several juz and 30 juz ), reciting the Koran individually (tadarusan), reciting the Koran with coaching, prayer (obligatory congregational prayers & sunnah prayers), religious lectures (Kajian), tabligh akbar, Friday sermons, weekly recitation, recitation of the yellow book, Batarbang, Haul teacher (Sheikh Samman, Sheikh Arsyad Al-Banjary, Teacher Sekumpul), memorizing and reciting Asmaul Husna, Maulid Habsyi, Maulid Burdah, Fardhu kifayah practice of taking care of "corpses", eclipse prayers, prayers and so on. Meanwhile, the model of religious education implemented in correctional institutions and detention centers in South Kalimantan is using the Sorogan method and Wetonan method, Bandongan method, halaqoh method, training method, pilot classes, seniors in matters of religion coaching juniors and bringing in resource persons from outside parties.